2017
DOI: 10.1007/s00280-017-3288-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of neoadjuvant chemoradiotherapy with intensity-modulated radiotherapy combined with gemcitabine and S-1 for borderline-resectable pancreatic cancer with arterial involvement

Abstract: Concurrent IMRT with gemcitabine and S-1 for patients is feasible as NACRT for BR-A with low gastrointestinal toxicity. IMRT can be employed as a standard radiotherapy to provide more effective NACRT with powerful chemotherapy drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
3
30
1
Order By: Relevance
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of 690 duplicates, a further 2588 articles were excluded after title and abstract screening because they did not meet the prespecified inclusion criteria. The full texts of the remaining 468 studies were evaluated in more detail, and 89 studies were found to meet the eligibility criteria for this systematic review. Among them, 22 studies containing information on clinical factors relevant to recurrence sites were selected for the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane Collaboration tool for assessing risk of bias showed that one study had no domain with a high risk of bias and three studies had one of seven domains with a high risk of bias ( Table S3 , supporting information). The overall risk of bias in non‐randomized studies, according to ROBINS‐I, was moderate in 48 studies and serious in 37 studies ( Table S4 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Potential disadvantages of neoadjuvant therapy include the following: A requirement for biliary decompression before chemotherapy and the potential for complications associated with biliary stents; delayed surgery, allowing progression to an unresectable stage in patients whose disease does not respond to therapy; and the potential for an increase in postoperative complications. Recently, results of randomized clinical trials and data analyses of preoperative therapy for borderline resectable and locally advanced PDAC have been reported (18)(19)(20)(21)(22). However, there have been few reports with high evidence levels on preoperative therapy for resectable PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with the disease are diagnosed at advanced stage, making them ineligible for curative treatment 2 - 4 . Even for patients with early stage disease, intrahepatic metastases were frequently occurred after curative resection 5 - 7 . In contrast, traditional chemotherapy and targeted therapy has been unsatisfactory in treatment of metastatic pancreatic cancer so far 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%